Transnational Educational Research in Four Countries: Promoting Critical Border Praxis - Cashman, Timothy (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2019)
This research took place in the following four countries: Malaysia, Mexico, Canada, and the United States (US). Educators in each country reported on how they addressed US international policies in their respective curricula. Critical border praxis emerged as a theoretical construct as a result of these transnational studies. Critical border praxis provides a contemplation of the intersection of place-based and border pedagogies, as well as how pedagogies are central to understanding one’s own situated-ness. The findings of this study include recommendations for additional in-depth discussions of international policies in the US social studies curriculum. Implications for educators elsewhere are also articulated.